2018
DOI: 10.1002/adma.201706369
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Mechanism Research and Methods for Electric‐Field‐Assisted Sintering of Ceramics

Abstract: Electric-field-assisted sintering of ceramic materials is under considerable attention during recent years. The current research is reviewed with a focus on mechanism research. Research of the mass transfer mechanisms in flash sintering (FS) is under debate during recent years. The research yields three main proposed mechanisms: nucleation due to movement of charged defects, Joule heating runaway, and electrochemical reactions. These are critically presented and discussed. Unlike FS, the mechanism of field-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 86 publications
0
56
0
Order By: Relevance
“…SPS is an effective method of sintering the Y-TZP material at relatively low temperatures that limits grain growth and contributes to full densification of the ceramic powders 52,71,72) . In this method, the high temperature levels as 3-10 thousands o C creates melting and evaporation of powder particle surfaces.…”
Section: Cs Ms and Spark Plasma Sintering (Sps)mentioning
confidence: 99%
“…SPS is an effective method of sintering the Y-TZP material at relatively low temperatures that limits grain growth and contributes to full densification of the ceramic powders 52,71,72) . In this method, the high temperature levels as 3-10 thousands o C creates melting and evaporation of powder particle surfaces.…”
Section: Cs Ms and Spark Plasma Sintering (Sps)mentioning
confidence: 99%
“…Since first reported in 2010 by Cologna et al, flash sintering has been demonstrated to be an innovative technique to densify ceramic compacts at low temperatures in very short time . In a typical flash sintering experiment, the sample is connected to an alternating current (AC) or direct current (DC) power supply and the electric field is directly applied to the sample, then the sample is heated in an ordinary furnace.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we want to know the feasibility of employing the flash sintering to prepare the 3YSZ/Al 2 O 3 ‐platelet composites. In addition, it is believed that the flash‐sintered 3YSZ/Al 2 O 3 ‐platelet composites would have the improved properties due to the finer grain size compared to the conventionally sintered samples …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations